Pengaruh Model Pembelajaran Mastery Learning terhadap Minat Belajar Pendidikan Agama Kristen Siswa Kelas XI SMK Negeri 1 Siborongborong Tahun Pembelajaran 2023/2024 - Emya Natalia Ginting; Oloria Malau; Tianggur Medi Napitupulu; Rida Gultom (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
The purpose of this study was to determine the positive and significant influence of the Mastery Learning model on the interest in learning Christian Religious Education of Class XI Students of SMK Negeri 1 Siborong in the 2023/2024 Academic Year. The method used in this study is a quantitative descriptive inferential statistical research method. The population is all class XI students of SMK Negeri 1 Siborong in the 2023/2024 Academic Year, totaling 367 people and a sample of 56 people is determined, which is 15% of the population. Data were collected using a positive closed questionnaire of 40 items. The results of the data analysis show that there is a positive and significant influence of the Mastery Learning model on the interest in learning Christian Religious Education of Class XI Students of SMK Negeri 1 Siborong Borong in the 2023/2024 Academic Year: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.525> rtable ( = 0.05, n = 56) = 0.226 thus it is known that there is a positive relationship between variable X and variable Y. b) Significant relationship test obtained tcount value = 4.529> ttable ( = 0.05, dk = n-2 = 54) = 2.000 thus there is a significant relationship between variable X and variable Y. 2) Influence test: a) Regression equation test, obtained regression equation Y ̂=